A gender analysis of development induced-displacement : exploring the impacts of resettlement on people's livelihoods at Run Ta Ek Techo Sen, Cambodia - Noeun, Nathamon; Chatterjee, Joyee S.; Kusakabe, Kyoko; Banerjee, Paula; Deutscher Akademischer Austausch Dienst (DAAD), Germany (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
Internal displacement is a global concern that affects millions of people, particularly women and marginalized communities. Displaced people face unique challenges in rebuilding their lives, including the loss of homes, livelihoods, and social roles. This study offers a gender lens analysis of the lived experiences of internally displaced persons (IDPs) in a resettled community, based on a comprehensive set of in-depth interviews and focus group discussions through a purposeful sampling. Drawing on a diverse range of 33 different voices from men and women, single parents, widows, unemployed youth, and elderly caregivers, the research examines how displacement disrupts livelihoods, traditional roles, exposes families to economic and social vulnerability, and reshapes their daily survival strategies. The findings reveal how displacement magnifies existing inequalities and financial struggles of these low income households. The study findings also emphasizes on how household structures is a major mediator of gender impacts. After relocation, both men and women experienced loss or changes of income which impact their family dynamic and labor allocation within the households. Men often face unstable and informal employment, sometimes relinquishing provider roles, while women disproportionately take on caregiving, food preparation, financial management, and child-rearing responsibilities which often without external support or recognition. Households have free access to health care services; yet, there still a continuous gender barriers in accesing health care which due to availability of the services and traditional gender roles. Education access is largely seen as improved, yet parental involvement remains shaped by traditional gender roles, with mothers staying behind to care for younger children while fathers work away from home. Coping strategies include subsistence farming, reliance on school feeding programs, informal trading, and dependence on remittances from migrating family members. These strategies reflect deep gendered expectations and adaptations to systemic gaps in access to livelihoods, education, and health care after relocation.Ultimately, the study calls for gender-sensitive programming and resettlement plannning that recognizes and responds to the often invisible labor and sacrifices made by displaced women and families. Additionally, it discusses how the internal displacement reflect and align with the goals and purposes of the UN Action Agenda on Internal Displacement and the Guiding Principles of IDPs. These findings emphasize the need to ensure that protection mechanisms are not only available but equitable and accessible, especially in contexts of displacement where women become responsible for the household survival and recovery.
A thesis submitted in patial fulfillment of the requirements for the degree of Master of Science in Gender and Development Studies
Thesis (M. Sc.) - Asian Institute of Technology, 2025
Keywords: Internally displaced persons -- Cambodia; Women -- Cambodia -- Social aspects